Carlos LLANO: Examen filosófico del acto de la decisión, México: Universidad Panamericana / Publicaciones Cruz O., S. A. 1998, 205 pp. - Ferrer Ortega, Guillermo (Universidad Panamericana. Facultad de Filosofía, 2000)
Carlos LLANO: Examen filosófico del acto de la decisión, México: Universidad Panamericana / Publicaciones Cruz O., S. A. 1998, 205 pp.
Keywords: Reseña